Computational investigation of advanced hub fairing configurations to reduce helicopter drag - Khier, W. (My University, 2014)
This paper reports research efforts carried out by the DLR within the framework of the European Commission “Clean Sky” Joint Technology Initiative (JTI) to reduce the aerodynamic drag of helicopters via the application of streamlined hub fairings. A number of three-dimensional RANS simulations of the flow past the GRC common platform fuselage using baseline hub and different generic full fairing shapes were carried out with the unstructured finite volume DLR solver TAU. The computations simulated forward flight at Mach number = 0.204 and an angle of attack ranging between -15° and 15°. Chimera overlapping grid method was used to transfer the solution between the fuselage and rotor hub grids, while Wilcox’s k-? two-equation model was employed to simulate the effects of turbulence. The results revealed significant contribution of blade attachments and stubs to hub drag. An overall drag reduction of 17-19% could be obtained by proper optimization of the fairing, blade attachments and stubs